Fatty acid composition of the internal mammary artery in relation to dietary intake of marine n-3 polyunsaturated fatty acids and association with flow-mediated vasodilation - Andreasen, J. J.; Aardestrup, I. V.; Eschen, R. B.; Obel, T.; Lundbye-christensen, S.; Schmidt, E. B. (Cellular and Molecular Biology, 2010)
Some evidence suggests that long-chain marine n-3 polyunsaturated fatty acids (n-3 PUFA) may increase production of vasodilatory nitric oxide from vascular endothelium. Fatty acids may therefore play a role for the left internal mammary artery (LIMA) graft function in coronary artery bypass grafting (CABG). However, little is known about the composition of fatty acids in the vessel wall of the LIMA. Using gas chromatography we investigated fatty acid composition in segments of the LIMA, in plasma nonesterified fatty acids (NEFA), in plasma phospholipid (PL) and in the pericardial adipose tissue (PAT) from 22 patients undergoing CABG. Furthermore, we investigated whether there was an association between the n-3 PUFA composition in LIMA and flow-mediated vasodilation (FMD). Self-reported fish consumption and supplementation of eicosapentaenoic acid and docosahexaenoic acids were reflected by the fatty acid composition in NEFA, PL and in PAT, but less so in the LIMA. There was no association between FMD and fatty acid composition of the LIMA.